Sustainable Development: Trends in Ukraine and the World - ZELINSKA, Halyna; ANDRUSIV, Uliana; DALIAK, Nadiia; DOVGAL, Olena; LAGODIIENKO, Volodymyr (Journal of Environmental Management and Tourism; Vol 12 No 5 (2021): JEMT Volume XII Issue 5(53) Fall 2021, 2021)
The paper studies sustainable development in the realities of Ukraine and the world. In particular, the global trends in human and sustainable development are analyzed. The tendencies of changes in the world measurement of human development are revealed through the human development index and partial indices characterizing the development for socio-economic inequality (IHDI), gender development (GDI), gender inequality (GII). It was found that sustainable development of society is impossible without solving the problem of a safe environment and preserving the environment for future generations. It has been determined that sustainable development presupposes the solution of triune tasks: economy, ecology and social sphere. It is noted that Ukraine has an extremely acute need for the transition to a sustainable development model, which is due to: a sufficiently large share of raw materials and energy-intensive types of production in the overall structure of the economy, which leads to the depletion of natural resources by a high level of environmental pollution, which negatively affects the health of the population. In terms of human development, significant differences remain between Ukraine and other countries when it comes to the well-being of the population, life expectancy and attitude to the environment. It was analyzed that the largest increase in the HDI rating for the period from 2010 to 2020 occurred in Ireland, the largest decrease in the HDI rating occurred in the Syrian Arab Republic and Libya, in countries affected by military conflicts. It has been determined that education is the primary and one of the most important factors for ensuring sustainable development of mankind. Attention is focused on solving the problem of creating an effective system for monitoring the environment, organizing an observation system, collecting, processing, transmitting, storing and analyzing information about the state of the environment, predicting its changes and making decisions on preventing negative changes in terms of its impact on public health. A model of ensuring human and sustainable development for Ukraine is proposed. The main directions of development should be the use of innovative approaches to environmental, demographic, educational and social components through the implementation of targeted regional development programs, outsourcing, insurance medicine, public-private partnerships, international educational online environment, international environmental projects.